Hull design and stability of ferry to Perhentian Island / Muhammad Syakir Mohd Ghazali - Mohd Ghazali, Muhammad Syakir (2023)
Perhentian Island, located off the northeastern coast of Malaysia, is a popular tourist destination known for its pristine beaches, crystal-clear waters, and abundant marine life. The current problem that occurs is the current which is Monohull type is unstable and the transportation service cant operate during Monsoon season.This study will recommend the best-suited Hull design to overcome the problem. The methodology that's been used in this study is Hull design and stability by software application and analysis through Excel. Based on the results, the ferry is stable after being analyzed by Initial stability, Trim calculation and GZ curve analysis. Overall the results show that this study is achieved the objective.